Inadimplência de dívida soberana em modelo de equilíbrio geral com credores heterogêneos - Souza, Tiago Carvalho Machado de (2012)
This paper provides a general equilibrium model of sovereign default with agents' heterogeneity, but without banking or foreign sectors. The heterogeneity is due to different kinds of consumers in the economy with distinct wealth shocks (but identical in other aspects) and the government, which decides whether or not to default, considers these agents differently in its welfare function. The intuition is that the default decision may be related to the bonds' owners (the distribution among agents) and not only the total resources borrowed or the economic activity. This approach matches empirical evidence which found a negative, though surprisingly weak, relationship between economic output and default. It also sheds light on other aspects that might influence the default decision, such as the existence and operation of secondary markets of public bonds.